Social aspects of two families from the Cajá II community in transassurini, Altamira, Pará, Brazil (Research, Society and Development, 2022)
The form where they live and if relates to the families with the community is what it takes in them to analyze the social aspects of two families of the community Cajá II, in the Project of Assurini Nesting, located in the agricultural zone of the city of Altamira-Pará. Leaving with this intention knowledge of the relations of work, of kinship, religious, spaces of sociability and cooperation was acquired. The structure of the families is of the nuclear type, where the relations between the component ones are leagued in such a way to the sanguineous bows in such a way to the affective ones. The distinction between the families is sufficiently clear, an example of this difference can be seen when the paper of the woman in each family is cited. While in one the woman these involved in all activities and decisions of the property, in the other the woman summarizes it the domestic tasks, without having active voice in the decisions. Finally, also they are gifts friendship and blood relations great with the neighborhood, mutual and remunerated. These types of relations direct and indirectly contribute for the progress of the community.